Knowledge assessment of the employees in Heart Center about the Psychological risk of the occupation in Al-Nasiriyah - Dhi-Qar Governorate during COVID 19 Pandemic: A cross-section study - Fatima. K. Abdulaali,; Alaa. K. Jasim,; Rajaa A. Mahmoud, (University of Thi-Qar Journal of Science, 2023)
The COVID-19 pandemic has created a massive psychosocial situation for healthcare professionals due toworkplace conditions. This study is to assess the knowledge of employees in Al-Nasiriyah heart center about psychological risk ofoccupational hazard during COVID-19 pandemic.Methodology:  A descriptive cross-sectional study includes random sample of 300 employee from Al-Nasiriyah heart center. A questionnaire was constructed according to five-point Likert scales by direct interviews. Results: 94.3% of employees’ response of knowledge about psychological risk of was found to be at statement number six “During Corona pandemic, as a health-care provider, you are afraid of transferring the infection to family members”. While 28% was found to be with the statement number 14: “The decision makers at the institution provide psychological support to the cadre at the heart center through material privileges and praise for their performance.” A statistical significance was found in the employees’ responses for all the statements included in the assessment except for the tenth one: "During Corona pandemic, as a health care provider, you feel afraid of quarantine and isolation": and statement number 13: "During Corona pandemic, as a health care provider, you feel job dissatisfaction as a result of  work pressures".Conclusions: most of employees in Al Nasiriyah Heart Center have good knowledge about the psychologicalhazard at the work place during COVID-19 pandemic including stress, fair from infection and fatigue from workloads.